Highly Efficient, Catalyst-Free, Diastereoselective, Diversity-Oriented Synthesis of Dihydrocoumarin–Pyrrolidine–Spirooxindoles Bearing Three Contiguous Stereocenters - Zuo, Xiong; Chen, Shuang; Xu, Sheng-Wen; Chang, Shun-Qin; Liu, Xiong-Li; Zhou, Ying; Yuan, Wei-Cheng (Synthesis, 2019)
A new methodology has been developed for the highly efficient diastereoselective construction of dihydrocoumarin–pyrrolidine–spirooxindole collections via a domino Michael/annulation reaction of 3-isothiocyanato oxindoles and coumarins under catalyst-free conditions. The resulting biologically important molecules bearing three pharmacophores and three contiguous stereocenters were obtained in up to 92% yield and >20:1 dr. It is noteworthy that utilization of a carboxylic acid activation/decarboxylation strategy represents an efficient approach for the domino Michael/annulation reaction of the chemically inert coumarin moiety. This protocol could expand candidate libraries, that will benefit the requirement for new bioactive molecules.
Keywords: dihydrocoumarins; pyrrolidines; spirooxindoles; 3-isothiocyanato oxindoles; catalyst-free